Myocardial infarction protective effect of xyloglucan on Drosophila melanogaster: A review - Monisha, K. M.; Dhanu, A. S.; Gopenath, T. S.; Pandeeswari, N.; Swamy, G. G.; Murugesan, Karthikeyan; Radhakrishnan, Anjuna; Murali, Uthamalingam; Elango, Boojhana; Basalingappa, Kanthesh M.; Mathanmohun, Maghimaa (Journal of Experimental Sciences, 2023)
Myocardial infarction, more often known as cardiac arrest, occurs when the supply of blood to the heart’s coronary artery decreases or ceases, causing damage to the heart muscle. Xyloglucan is a plant polysaccharide. Xyloglucan has been proven in several studies utilizing model organisms to reduce the risk of coronary heart disease by avoiding post-occlusion phases inhibiting apoptosis and enhancing energy metabolism. Many studies utilize Drosophila melanogaster because its SRY-related HMG-box 5 (SOX5) gene encodes a SOX family transcription factor; the human SOX5 ortholog, Sox102F, is well conserved in Drosophila melanogaster. Suppressing Sox102F in flies resulted in significant heart dysfunction, structural defects, and a disturbance in notch signal transduction. This demonstrates that SOX5 serves an important functional part in the heart and that variations in SOX5 concentrations may contribute to the possibility of myocardial infarction. Xyloglucan activity is significant in myocardial infarction and may be lowered in the myocardium after H/R damage by stimulating Notch signaling, which may benefit myocardial survival, angiogenesis, and cardiac function. This review discusses the roles of the human SOX5 and Drosophila SOX102F genes, the notch signaling system, and how xyloglucan in tamarind seeds may defend against heart damage by preventing apoptosis along with improving energy metabolism.